ANALISIS KEKUATAN RASIO KEUANGAN UNTUK MEMPREDIKSI KONDISI FINANCIAL DISTRESS (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2021) - Yuniarti, Yuniarti (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2023)
This study aims to analyze the power of financial ratios in predicting the occurrence of financial distress. The financial ratio variables used in this research are liquidity ratios, profitability ratios, leverage ratios, and operating cash flow ratios. This research is associative, using purposive sampling method. Manufacturing companies are the population in this study with the results of 165 research sample data. The analysis technique used in this study is logistic regression. There are five variables used in this study: financial distress as the dependent variable, while the liquidity ratio, profitability ratio, leverage ratio and operating cash flow ratio as the independent variable. The results of this study indicate that the liquidity ratio proxied by CR has a significant negative effect on financial distress, the profitability ratio proxied by ROA has a significant negative effect on financial distress. leverage proxied by DER has no significant effect on financial distress, the operating cash flow ratio has no effect on financial distress. Based on these results, management is expected to be able to make the right decisions to improve conditions of financial difficulties that lead to potential bankruptcy.